Penyuluhan Hukum Tentang Pelestarian Lingkungan Hidup Dan Aksi Pendukungnya - Deassy Jacomina Anthoneta Hehanussa; Vica Jillyan Edsti Saija; Marthinus Johanes Saptenno (Faculty of Law Pattimura University, 2022)
Introduction: Maluku is an area with an archipelagic character because the ocean is more expansive than the land so natural resources in the sea need to be preserved.Purposes of Devotion: To provide legal understanding to the community about their participation in environmental conservation, in this case, natural resources in Ambon Bay. Method of Devotion: The method used is legal counseling to the community and action to villages and traditional villages that are service partners.Results of the Devotion: It is known that the community does not yet have a high awareness of environmental conservation, in this case, the ocean. This can be seen with the garbage found in Ambon Bay. Thus, the ocean has not been interpreted as an area that produces natural resources for now and the future. In contrast, the village government as the bottom line of government has made efforts to appeal to the community.